Analysis Of Factors Hindering The Level Of QRIS Usage In The MSME Sector In Palu City - Putri Dea Rizky; Darman Darman; Vitayanti Fattah; Suryadi Samudra (UNIVED Press, 2026)
The use of QRIS by MSMEs in Palu City is still suboptimal, so it is important to identify factors that hinder its utilization. This study aims to analyze digital literacy barriers, technological infrastructure barriers, and risk perception barriers on QRIS adoption rates. A quantitative approach was used, involving 75 respondents obtained through purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using linear regression with SPSS.The results showed that only risk perception barriers significantly influenced QRIS adoption rates, while digital literacy and technological infrastructure barriers showed no significant impact. An R2 value of 0.149 indicates that the model only explains a small portion of the variation in QRIS usage. This finding confirms that digital security and trust remain key factors for MSMEs adopting QRIS. Consequently, improving digital security literacy and strengthening data protection need to be prioritized by local governments and Bank Indonesia to encourage wider QRIS adoption.